Effects of blue NPK fertilizer and/or biochar on the growth and yield of okra (Abelmoschus esculentus L.) plant using Silabukan soil - Sauti, Mohamad Suhaizrezal; Azman, Elisa Azura; Ismail, Roslan; Phooi, Chooi Lin; Lakulassa, Safikah (Politeknik Negeri Lampung, 2024)
This study aims to evaluate the impact of using organic material in the form of biochar as an additional fertilizer on the growth and productivity of okra plants (Abelmoschus esculentus L.). The research method involves treatments with the application of blue NPK fertilizer at a rate of 300 kg ha-1 and biochar at a rate of 3 tons ha-1. The fertilizer used in the study is blue NPK fertilizer (12:12:17) is 0, 100, 200, 300, 400 kg ha-1 and biochar is 0, 2, 3 t ha-1. The results reveal that the combination of organic and inorganic fertilizers leads to higher growth of okra plants, with the tallest plant height and the highest leaf count recorded in this treatment. Furthermore, the use of biochar enhances leaf and flower formation in okra plants, reduces soil erosion, and improves water retention. The analysis of phosphorus availability in the soil also indicates an increase after the application of blue NPK fertilizer and biochar. Overall, biochar has a positive impact on the growth and productivity of okra plants as well as soil quality.